Computational analysis for the determination of deleterious nsSNPs in human MTHFD1 gene. (October 2017) - Desai, Mansi; Chauhan, J.B.
Graphical abstract: Highlights: The functional and structural consequences of nsSNPs of human MTHFD1 gene was analyzed using computational tools. Among 45 deleterious SNPs, 17 predicted highly conserved & functional while 17 predicted highly conserved & structural. Among 45 most significant SNPs, 15 were predicted to be involved in post translational modifications. The p.Asn439Lys and p.Asp445Asn present within cesium cation and potassium binding sites respectively. The two SNPs (p.Asp562Gly and p.Gly637Cys) present within ligand binding sites. Abstract: Single nucleotide polymorphisms (SNPs) are the most common genetic polymorphisms and play a major role in many inherited diseases. Methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) is one of the enzymes involved in folate metabolism. In the present study, the functional and structural consequences of nsSNPs of human MTHFD1 gene was analyzed using various computational tools like SIFT, PolyPhen2, PANTHER, PROVEAN, SNAP2, nsSNPAnalyzer, PhD-SNP, SNPs&GO, I-Mutant, MuPro, ConSurf, InterPro, NCBI Conserved Domain Search tool, ModPred, SPARKS-X, RAMPAGE, FT Site and PyMol. Out of 327 nsSNPs form human MTHFD1 gene, total 45 SNPs were predicted as functionally most significant SNPs, among which 17 were highly conserved and functional, 17 were highly conserved and structural residues. Among 45 most significant SNPs, 15 were predicted to be involved in post translational modifications. The p.Gly165Arg may interfere in homodimer interface formation. The p.Asn439Lys and p.Asp445Asn may interfere in binding interactions of MTHFD1 protein with cesium cation and potassium. The two SNPs (p.Asp562Gly and p.Gly637Cys) might interfere in interactions of MTHFD1 with ligand.